THE EFFECT OF ORGANIZATIONAL CULTURE AND WORK DISCIPLINE ON THE PERFORMANCE OF HEALTH WORKERS AT MUSLIMAT MOTHER AND CHILD HOSPITAL, JOMBANG - Kusumaningdiah Sekar Jatiningrum; Ratna Wardani; Joko Prasetyo (RADJA PUBLIKA, 2026)
The performance of health workers reflects employees’ work outcomes in terms of both quantity and quality. A decline in health workers’ performance, or failure to meet hospital expectations, may negatively affect the quality of hospital services. Organizational culture adopted by an institution plays a crucial role in determining performance quality. In addition to organizational culture, work discipline is also a factor that influences performance. High work discipline is associated with improved performance. This study aimed to analyze the effect of organizational culture and work discipline on the performance of health workers at Muslimat Mother and Child Hospital, Jombang. This study employed a quantitative research design with a cross-sectional approach. The independent variables were organizational culture and work discipline, while the dependent variable was the performance of health workers. The population consisted of all health workers at Muslimat Mother and Child Hospital, Jombang, totaling 132 individuals. Using proportional random sampling, a sample of 100 respondents was obtained. Data were analyzed using logistic regression analysis. The results showed that organizational culture had a significant effect on the performance of health workers at Muslimat Mother and Child Hospital, Jombang (p = 0.000). Work discipline also had a significant effect on health workers’ performance (p = 0.000). Furthermore, organizational culture demonstrated a statistically significant influence on health workers’ performance (p = 0.004; OR = 0.023; 95% CI = 0.002–0.290), with a Nagelkerke’s R Square value of 0.934. Organizational culture plays an important role in influencing the quality of health workers’ performance, as it shapes values, norms, and collective behaviors, creates an environment that encourages collaboration, innovation, and work comfort, and indirectly enhances discipline and motivation, leading to improved performance.